Integrated open-water mussel ( Mytilus planulatus ) and Atlantic salmon ( Salmo salar ) culture in Tasmania, Australia - Cheshuk, BW; Purser, GJ; Quintana, R (Aquaculture, 2003)
In a field experiment, Tasmanian blue mussels (Mytilus planulatus) were cultured within an Atlantic salmon (Salmo salar) farm in North West Bay (NWB), Tasmania to test if enhanced mussel performance and reduced organic enrichment resulted from integrated mussel-salmon culture. The performance of mussels grown within the fish farm lease (70 and 100 m from the fish cages) was not appreciably different from that of mussels grown distant to the farm (500 and 1200 m from the fish cages). After culturing mussels for 14 months, no difference among culture sites was indicated for any measured parameter except shell length (P < 0.0001) and condition index (P < 0.01). However, these differences among culture sites were minor, with final mean shell lengths and condition index being within 2.0 mm and 11, respectively. Growth of mussels cultured within the fish farm was not enhanced due to several contributing factors: (a) solid wastes (feed particles and faeces) from the farm did not significantly increase particulate food concentrations above ambient levels, (b) phytoplankton production within the farm was not enhanced, (c) mussels were cultured too distant to intercept settling particulate wastes emanating from the fish cages, and (d) ambient seston concentrations were consistently above the pseudofaeces threshold concentration, thereby limiting ingestion of fish farm particulate wastes. 2003 Elsevier Science B.V. All rights reserved.